Does the Netherlands-based consumer disidentification model work in the US? - Prince, Melvin; Kwak, Lynn (EMPGENS | Journal of Empirical Generalisations in Marketing Science, 2020)
Alexander Josiassen (2011) initiated research on the consumer disidentification (CDI) concept and its impact on product purchase behavior. In his investigation, a predictive model that included CDI as an exogeneous factor in domestic product preference was tested on adult second-generation immigrants who were born in, and lived in, the Netherlands. The model also incorporated consumer ethnocentrism (CET) as a second predictor variable. Josiassen's study showed that CDI negatively affected the purchase of products made domestically or by domestic firms. Conversely, CET was found to have a positive effect on the purchase of these products. Furthermore, relationships of CDI and CET to purchase intentions were independent of each other. In the Netherlands model, both variables were hypothesized to explain domestic product preference directly and indirectly through domestic product judgment. This paper replicates and assesses the generalizability of the CDI construct and model. Replication of the Netherland CDI model in the U.S. results in an acceptable measurement fit, but a slightly below acceptable structural fit. © 2020, University of South Australia. All rights reserved.
Keywords: Consumer disidentification; Cross-cultural; Domestic product preference; Ethnocentrism; Second-generation immigrants; dept.mkt; peer-reviewed; ⛔ No DOI found